2017
DOI: 10.1016/j.is.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Formulating and managing viable SLAs in cloud computing from a small to medium service provider's viewpoint: A state-of-the-art review

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Presents a state of the art review on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…In this form of service management, service providers constantly monitor the SLOs after the SLA has been formed to ensure that possible violations are averted before they occur. In our previous work [5], we observed that this proactive management after an SLA has been formed but before violation occurs works well for large scale cloud service providers. This is because large providers have abundant resources and can easily obtain additional resources if/when required to avert possible violations as they are detected.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this form of service management, service providers constantly monitor the SLOs after the SLA has been formed to ensure that possible violations are averted before they occur. In our previous work [5], we observed that this proactive management after an SLA has been formed but before violation occurs works well for large scale cloud service providers. This is because large providers have abundant resources and can easily obtain additional resources if/when required to avert possible violations as they are detected.…”
Section: Introductionmentioning
confidence: 92%
“…This may not be true in all cases, especially when the business is a small to medium (SME) cloud service provider. Unlike large scale cloud service providers, such as Amazon, an SME has a finite quantity of computing resources with which to manage their users' requests [5]. As shown in the literature, these issues between a service provider and service user are addressed by defining and managing a Service Level Agreement (SLA).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, QoS is one of the primary factor in forming a viable SLA and for establishing a reliable relationship between two parties. There are substantial amount of literatures discussing about the topic [8][9][10][11][12][13][14]. We have divided these approaches into three classes based on their functionality and working attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cloud computing allows consumers to share and access for daily applications/sensitive information without coordination and synchronization mode. These applications provide important data and control information to users at suitable time and without any delay [3,4].…”
Section: Introductionmentioning
confidence: 99%